Intratympanic steroid administration and predictors of recovery in sudden sensorineural hearing loss - Devin J. Kennedy; Erin Williams; Lucienna Wolf; Jacquelyn Golden; Addison Lana; Matthew Wiefels; Madeline Pyle; Valerie Yunis; Michael Hoffer (PLoS ONE, 2025)
Objectives Sudden sensorineural hearing loss patient outcomes remain highly variable despite established treatment modalities. This study investigates the effects of treatment modalities, individual-level risk factors, and clinical presentation on sudden sensorineural hearing loss recovery. Methods Retrospective chart review of n = 231 patients who initiated intratympanic steroids between 01/01/2015-01/01/2025 following sudden sensorineural hearing loss. We collected individual-level risk factors and comprehensive audiometric data. Logistic and linear regression analyses were performed to identify relationships between patient, disease, and treatment-related variables to audiometric recovery (pure-tone average and word recognition score). Segmented linear regression analysis was used to assess the influence of intratympanic steroid treatment delay on patient recovery. Recovery outcomes were determined in accordance with American Academy of Otolaryngology-Head and Neck Surgery criteria. Results Earlier intratympanic steroid initiation following sudden sensorineural hearing loss symptom onset significantly predicted increased pure-tone average recovery (p < 0.001) irrespective of intratympanic steroid status as primary treatment or as salvage therapy following oral steroids. Intratympanic steroid efficacy significantly diminished if initiated beyond 18 days following symptom onset (p < 0.001). Total number of intratympanic received and time between subsequent intratympanic injections did not impact recovery. Patient-level factors including demographics, socioeconomic status, medical and social risk factors, and medical comorbidities were largely found to have no significant relationship with recovery. Increased initial pure-tone average was associated with poorer overall pure-tone average recovery (p < 0.001). The presence of initial serviceable hearing predicted worse final recovery status (p = 0.01). Bilateral sudden sensorineural hearing loss showed significantly worse pure-tone average recovery compared to unilateral sudden sensorineural hearing loss (p = 0.04). Conclusion Intratympanic steroids are an effective treatment option for sudden sensorineural hearing loss. Clinicians should be mindful of intratympanic steroid initiation timing and case-specific factors that may influence sudden sensorineural hearing loss recovery when treating patients with sudden sensorineural hearing loss.